PERANCANGAN SISTEM INFORMASI PEMBAYARAN KEUANGAN BERBASIS WEB DI SMK NEGERI 4 PADANG - Nisa, Ardina Khairun; Mary, Thomson; Kurniawan, Haris (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The financial payment information system at SMKN 4 Padang still uses manual methods, which causes various obstacles such as recording errors, reporting delays, and a lack of transparency in the transaction process. To overcome this problem, a digital-based financial payment information system was designed using the Software Development Life Cycle (SDLC) Waterfall model method. This model was chosen because it provides a systematic and structured approach to software development, starting from the requirements analysis stage, system design, implementation, testing, to maintenance. The aim of this research is to design and build a computerized, web-based financial payment information system to increase efficiency and accuracy in school financial management. The result of this research is an information system that is able to manage student payments more accurately and efficiently. This system provides features for automatically recording transactions, creating real-time financial reports, as well as better accessibility for school administration and students.